2007
DOI: 10.1007/s10495-007-0138-9
|View full text |Cite
|
Sign up to set email alerts
|

An altered fibronectin matrix induces anoikis of human squamous cell carcinoma cells by suppressing integrin alpha v levels and phosphorylation of FAK and ERK

Abstract: Fibronectin regulates many cellular processes, including migration, proliferation, differentiation, and survival. Previously, we showed that squamous cell carcinoma (SCC) cell aggregates escape suspension-induced, p53-mediated anoikis by engaging in fibronectin-mediated survival signals through focal adhesion kinase (FAK). Here we report that an altered matrix, consisting of a mutated, nonfunctional high-affinity heparin-binding domain and the V region of fibronectin (V+H-), induced anoikis in human SCC cells;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 73 publications
2
31
0
1
Order By: Relevance
“…Hence, the RGD sequence by itself elicits weaker integrin activation than full length adhesion proteins [20,21]. For example, integrin binding to full length FN and VN activates the downstream signaling molecules FAK and ERK [31], leading to the induction of osteogenic gene expression [32], alkaline phosphatase activity, calcium deposition [33,34], and runx2 activation [33]. In contrast, cell adhesion to RGD was shown to activate FAK, but not ERK [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the RGD sequence by itself elicits weaker integrin activation than full length adhesion proteins [20,21]. For example, integrin binding to full length FN and VN activates the downstream signaling molecules FAK and ERK [31], leading to the induction of osteogenic gene expression [32], alkaline phosphatase activity, calcium deposition [33,34], and runx2 activation [33]. In contrast, cell adhesion to RGD was shown to activate FAK, but not ERK [35].…”
Section: Discussionmentioning
confidence: 99%
“…The fibronectins themselves are large extracellular matrix glycoproteins often found in the plasma and other body fluids. They participate in cell adhesion, migration, invasion, and survival by activating integrin and proteoglycan receptors thru specific signalling pathways such as the extracellular signal-regulated kinase (ERK) (Kamarajan and Kapila 2007). Studies using an altered fibronectin protein showed that SCC cells escape suspensioninduced death (anoikis) by forming multicellular aggregates which avail themselves of fibronectin survival signals mediated by integrin αV and focal adhesion kinase activation (Zhang, Lu et al 2004).…”
Section: Extracellular Matrix Can Profoundly Influence Tumour Progresmentioning
confidence: 99%
“…Disruption of FAK signaling by various techniques induces cell death in cancers after the induction of cell rounding and detachment from the substratum. It was also reported that anoikis was associated with reduced levels of FAK [21,22].…”
Section: Introductionmentioning
confidence: 99%